Agricultural Grand March - E. Mack::::::::: (Lee & Walker)
Piano score, 5 p. Cover title: Agricultural March cover lithograph of the Agricultural Building by T. Sinclair & Son, Philadelphia, drawn by A.G. Score c1876 by Oliver Ditson & Co. (J.E. Ditson was successor to Lee & Walker.) Publishers advertisement on verso of last leaf.